STRATEGY OF MANAGEMENT OF ISLAMIC BOARDING SCHOOL EDUCATION IN IMPLEMENTING RELIGIOUS MODERATION - Hendrayadi, Hendrayadi; Yunus, Yunus (STKIP Pesisir Selatan, 2025)
Islamic boarding school education management has a vital role in instilling the values ​​of religious moderation in students. Through the development of an adaptive curriculum, increasing the capacity of educators, creating a conducive environment, and partnerships with various parties, Islamic boarding schools can be at the forefront of producing a generation of Muslims who are noble, have broad insights, and are able to maintain harmony and peace in a pluralistic society. The implementation of religious moderation in Islamic boarding schools is not only the internal responsibility of the Islamic boarding school, but also a long-term investment for the future of a peaceful and harmonious Indonesian nation. Religious Moderation inIslamic Boarding School in North Luwucontained in the following values; 1) Tawassut (middle way), 2) Tawazun (balanced) 3) I'tidal (fair) 4) Tasamuh 5) Musawah; 6) Syura (deliberation) 7) Islah (reform) 8) Tatawwur wa ibtikar (dynamic and innovative) 9) Tahaddur (civilized), 10) Wataniyah wa muwatanah 11) Qudwatiyah (exemplary or pioneering).